2009
DOI: 10.3899/jrheum.090354
|View full text |Cite
|
Sign up to set email alerts
|

The OMERACT Ultrasound Task Force — Advances and Priorities

Abstract: This article reports the most recent work of the OMERACT Ultrasound Task Force (post OMERACT 8) and highlights of future research priorities discussed at the OMERACT 9 meeting, Kananaskis, Canada, May 2008. Results of 3 studies were presented: (1) assessing intermachine reliability; (2) applying the scoring system developed in the hand to other joints most commonly affected in rheumatoid arthritis (RA); and (3) assessing interobserver reliability on a deep target joint (shoulder). Results demonstrated good int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0
4

Year Published

2011
2011
2016
2016

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 68 publications
(31 citation statements)
references
References 8 publications
1
26
0
4
Order By: Relevance
“…Results confirmed that a consensus scoring system of synovitis based on consensus definitions, combined with a standardized acquisition protocol, provided good intra-and inter-reliability 21,22 . In order to be able to make assumptions on global disease activity, it is necessary to move from the level of single joints to the level of the patient as a global entity.…”
Section: Journal Of Rheumatologysupporting
confidence: 60%
See 1 more Smart Citation
“…Results confirmed that a consensus scoring system of synovitis based on consensus definitions, combined with a standardized acquisition protocol, provided good intra-and inter-reliability 21,22 . In order to be able to make assumptions on global disease activity, it is necessary to move from the level of single joints to the level of the patient as a global entity.…”
Section: Journal Of Rheumatologysupporting
confidence: 60%
“…Our Task Force has worked towards the development of a reliable standardized scoring system for synovitis in RA that is applicable to all joints and is consistent between machines, and which combines GS and PD in a semiquantitative 0-3 scale 21,22 . Results confirmed that a consensus scoring system of synovitis based on consensus definitions, combined with a standardized acquisition protocol, provided good intra-and inter-reliability 21,22 .…”
Section: Journal Of Rheumatologymentioning
confidence: 99%
“…Results confirmed that the OMERACT ultrasound definitions and scoring system of synovitis combined with a standardized acquisition protocol provided good intra-and interobserver reliability. This work was presented at OMERACT 8 9 .…”
Section: Journal Of Rheumatologymentioning
confidence: 99%
“…Over the last decade, the OMERACT MSUS group has assessed the metric properties of US in detecting and scoring potential endpoint in rheumatic diseases for clinical trials and practice [24][25][26][27][28]. The group has worked on validation of US-detected and graded tendon damage in RA [19,20], which is an essential component of the structural damage in this disease [19,20].…”
Section: Discussionmentioning
confidence: 99%